(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
In spite of the fact that psychology is entangled with a broad range of other disciplines ofresearch, the major focus of this analysis will be on the links that exist between psychology and otherbranches of the social sciences. In contrast to this, the study of psychology is deeply linked with a vastnumber of other subfields of inquiry. Although these fields of study can include fields like sociology,political science, economics, and social anthropology, they are by no means confined to these fields. InThis study be pleasantly pleased to learn that psychology is a broad and deep subject that may provideyou with a wealth of intriguing and applicable information. Other fields of research, such as linguistics,law and jurisprudence, geography, history, economics, communication studies, and a great deal moreare included under the umbrella of the social sciences. In addition to linguistics and political science,this area also include sociology, international relations, political science, law and jurisprudence, andlaw. In recent years, the subfield of sociology has been the focus of the majority of research anddiscussion.